2003
DOI: 10.1677/joe.0.1780319
|View full text |Cite
|
Sign up to set email alerts
|

Both estrogen and raloxifene cause G1 arrest of vascular smooth muscle cells

Abstract: The proliferation of vascular smooth muscle cells (VSMC) is a crucial pathophysiological process in the development of atherosclerosis. Although estrogen is known to inhibit the proliferation of VSMC, the mechanism responsible for this effect remains to be elucidated. In addition, the effect of raloxifene on VSMC remains unknown. We have shown here that 17 -estradiol (E 2 ) and raloxifene significantly inhibited the platelet-derived growth factor (PDGF)-stimulated proliferation of cultured human VSMC. Flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 57 publications
(49 reference statements)
0
36
2
Order By: Relevance
“…[39][40][41] It has also been reported that stimulation of GPR30 blocks VSMC proliferation. 37,42 The vasodilator action of G-1 may be mediated by NO-independent 40 and NO-dependent 37,39,40 pathways; the latter involves GPR30-induced endothelial NO synthase (eNOS) phosphorylation. 43 Also, G-1 decreases nicotinamide adenine dinucleotide phosphate-stimulated superoxide production by the carotid and intracranial arteries, indicating the scavenging effects of GPR30 on superoxide anions.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…[39][40][41] It has also been reported that stimulation of GPR30 blocks VSMC proliferation. 37,42 The vasodilator action of G-1 may be mediated by NO-independent 40 and NO-dependent 37,39,40 pathways; the latter involves GPR30-induced endothelial NO synthase (eNOS) phosphorylation. 43 Also, G-1 decreases nicotinamide adenine dinucleotide phosphate-stimulated superoxide production by the carotid and intracranial arteries, indicating the scavenging effects of GPR30 on superoxide anions.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…Once 5 ϫ 10 3 or 8 ϫ 10 3 cells/well were plated in a 96-well plate, they were first incubated for 24 h in M199 with 10% FCS and then switched to phenol red-free M199 with 10% FCS for 2 days and phenol red-free M199 with 0.4% FCS for 24 h. Cell viability was assessed after a 24-h incubation with the LPS/cytokine mixture in the presence or absence of 1 M raloxifene. The number of surviving cells was assessed as described elsewhere (Takahashi et al, 2003) by recording the absorbance at 490 nm generated by the bioreduction of the MTS tetrazolium compound into a colored soluble formazan product (Cell Titer 96 AQueous One Solution Cell Proliferation Assay; Promega, Madison, WI).…”
Section: Vascular Action Of Raloxifene 1445mentioning
confidence: 99%
“…2), in part through direct inhibition of gene expression of cyclin D1 followed by dephosphorylation of Rb and suppression of E2F activity mediated by ERa in a transcription-dependent manner, a so-called genomic mechanism [38] as reported the effect of estrogen on Rb phosphorylation [39,40], and in part due to induction of apoptosis through a p38 cascade whose activation is mediated by ERa in a transcriptionindependent manner, a so-called nongenomic mechanism [41] (Fig. 3).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%